Task-Dependent Compression Performance Assessment in Body Physiology Signals - Ileri, Fatih; Gokcay, Didem (2020 28th Signal Processing and Communications Applications Conference (SIU), 2020)
Compression of biological signals have great importance in storing, ofﬂine processing, and transmission of these signals to other entities. There have been many researches based on assessing the performance of newly published compression methods. Main performance metrics used in these researches are the compression ratio (CR) and the error metric, generally the PRD (percent mean square difference). In this research we assess the performance of our compression method in a task-dependent fashion. We applied a neural network based classiﬁcation on original and compressed EMG signals, collected from subjects participated a deﬁned task. With this approach, we were able to understand what amount of necessary information of EMG signals is suppressed during compression.